Frugivoria e dispersão de sementes de Talauma ovata (Magnoliaceae) no sudeste brasileiro - Cazetta, Eliana [UNESP]; Rubim, Paulo [UNESP]; Lunardi, Vitor de Oliveira; Francisco, Mercival Roberto; Galetti, Mauro [UNESP] (My University, 2002)
Some plants are widely distributed, ranging in different vegetation types. Since bird distribution can be directly associated to vegetational cover, we expect that seed dispersers can also vary following phytophysiognomy for some ornithochorous plants. The purpose of this paper was to describe potential seed disperser birds of Talauma ovata (Magnoliaceae) in semideciduous Atlantic forest and cerrado fragments in south-east Brazil. In 79 h of focal observations we recorded 1085 visits of 25 different bird species consuming T. ovata diaspores. Although most bird species observed consuming T. ovata diaspores present generalist habits, they were potential seed dispersers, presenting high visits rate and do not staying a long time on the plants, favoring seed dispersal efficiency. Fruit consumption was not different between species in the study sites and the time spending on the plants was not different between species in semideciduous forest, but was different in cerrado. Agonistic encounters were observed mainly in the end of fruiting season, but was not relevant to decrease the number of seeds dispersed by birds. The occurrence of different potential seed dispersers between areas, such as Cyanocorax cristatellus (Corvidae), Schistochlamys ruficapillus (Emberizidae) and Mimus saturninus (Mimidae), which are endemic from the cerrado ecosystem and could rarely be found in semideciduous forest, suggests that seed dispersers can vary according to phytophysiognomy characteristics. Our results also indicate that the evolution of a generalist seed dispersal system such as observed for T. ovata can make possible the colonization of different ambients. Furthermore, the high number of visits recorded for both areas suggests that the fleshy arils of T. ovata are important feeding resources for birds.
Frugivory and seed dispersal of Talauma ovata (Magnoliaceae) in south-east Brazil
Keywords: Frugivory; Ornithochory; Seed dispersal; Talauma ovata; Aves; Corvidae; Cyanocorax cristatellus; Emberizinae; Magnoliaceae; Mimidae; Mimus saturninus; Schistochlamys ruficapillus